A Novel Framework for Understanding the Pattern Identification of Traditional Asian Medicine From the Machine Learning Perspective - Hyojin Bae; Sanghun Lee; Sanghun Lee; Choong-yeol Lee; Chang-Eop Kim (Frontiers in Medicine, 2022)
Pattern identification (PI), a unique diagnostic system of traditional Asian medicine, is the process of inferring the pathological nature or location of lesions based on observed symptoms. Despite its critical role in theory and practice, the information processing principles underlying PI systems are generally unclear. We present a novel framework for comprehending the PI system from a machine learning perspective. After a brief introduction to the dimensionality of the data, we propose that the PI system can be modeled as a dimensionality reduction process and discuss analytical issues that can be addressed using our framework. Our framework promotes a new approach in understanding the underlying mechanisms of the PI process with strong mathematical tools, thereby enriching the explanatory theories of traditional Asian medicine.